2021
DOI: 10.1186/s13059-021-02552-3
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking UMI-based single-cell RNA-seq preprocessing workflows

Abstract: Background Single-cell RNA-sequencing (scRNA-seq) technologies and associated analysis methods have rapidly developed in recent years. This includes preprocessing methods, which assign sequencing reads to genes to create count matrices for downstream analysis. While several packaged preprocessing workflows have been developed to provide users with convenient tools for handling this process, how they compare to one another and how they influence downstream analysis have not been well studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 85 publications
(92 reference statements)
4
47
0
Order By: Relevance
“…As sc/snRNA-seq technologies continue to rapidly develop, improving methods used to analyze the resulting data will require ongoing benchmarking of methods to identify the strengths of existing techniques and areas for improvement in future approaches. For example, a recent study by You et al ( 26 ) evaluated many different pipelines for the preprocessing of UMI-based scRNA-seq data. Concordant with the current paper, You et al ( 26 ) found ’s performance to be excellent, both computationally and in terms of the accuracy and robustness of the resulting counts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As sc/snRNA-seq technologies continue to rapidly develop, improving methods used to analyze the resulting data will require ongoing benchmarking of methods to identify the strengths of existing techniques and areas for improvement in future approaches. For example, a recent study by You et al ( 26 ) evaluated many different pipelines for the preprocessing of UMI-based scRNA-seq data. Concordant with the current paper, You et al ( 26 ) found ’s performance to be excellent, both computationally and in terms of the accuracy and robustness of the resulting counts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study by You et al ( 26 ) evaluated many different pipelines for the preprocessing of UMI-based scRNA-seq data. Concordant with the current paper, You et al ( 26 ) found ’s performance to be excellent, both computationally and in terms of the accuracy and robustness of the resulting counts. However, they report that — at least when using pseudoalignment with structural constraints — and demonstrate a left-skew in the count distribution of pseudogenes and therefore may underestimate the abundance of transcripts labeled with this biotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many methods have been proposed for single-cell RNA-seq normalization (Cole et al 2019; Tian et al 2019; You et al 2021; Lytal, Ran, and An 2020; Borella et al 2021; Ahlmann-Eltze and Huber 2021; Breda, Zavolan, and van Nimwegen 2021), the approach of equalizing depth for all cells, often to a “size factor” such as ten thousand (CP10k) or one million (CPM), followed by the application of a variance stabilizing transform like log plus one (log1p) is most popular. These methods are implemented in the widely used Seurat 1 and Scanpy (Wolf, Angerer, and Theis 2018) programs, but they do not explicitly model cell depth as a covariate.…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge that these first steps must often vary greatly depending on the biological context, and invite the user to validate optimized custom preprocessing workflows for that context. Comprehensive reviews of preprocessing pipelines for scRNA-seq data have been previously published [43][44][45] .…”
Section: Key Considerations For Nmf Analysismentioning
confidence: 99%